Analysis of Pasig River hydraulics for resource use and conservation management - Sumagaysay, Liezl Anne R.
The manner that Pasig River conveys water and other materials into and from Manila Bay and Laguna Lake affects the use suitability of water in the river and in Laguna Lake. Data analysis and modeling of Pasig River was done for resource use and conservation management through 1-D river hydraulic modelling using HEC-RAS 4.1. Actual data on water levels of Manila Bay and Laguna Lake, along with data on water levels of a river station, lateral inflows, Manning coefficients, dispersion coefficient limits, minor losses and salinity conditions along Pasig river, were used the boundary, initial, calibration and validation infonnation in the model simulations. Numerical simulation analysis revealed that when the tidal levels at Manila Bay averages at least 20-35cm (depending on the lake stage) higher than that of Laguna Lake water levels, backflow that can reach more than 200 m3/s can be expected to occur. Along with the backflow, lake saltwater intrusion can also be expected. With the available simulated salinity distribution along Pasig River, river concentrations were compared and related to monitored salinity plume coverage in the Lake. Results of the analysis of the Pasig River hydraulics in this study provide valuable information for the reoperation of Napindan Hydraulic Control Structure. The model was also used to come up with a hydro matrix of the Lake when it serves as a flood detention basin during the wet season. Recession times of flood waters in the lake were also computed for different lake stages, using information on the river discharge (that can reach more than 800 m3/s) as determined through the model. Considering the importance of Pasig River hydraulics on the environmental condition of Laguna Lake, results of this study serve as valuable input to the resource use and conservation management of both ecosystems.